Some aspects of business ethics in family enterprises in Slovenia - Duh, Mojca (Organizacija (Kranj), 2007)
At the most basic level a family enterprise may be defined as an enterprise, which is controlled by members of a single family. But family enterprises are not homogenous. They vary in terms of degrees of family involvement. The research cognitions described in the present paper show that 30.9 % of the observed enterprises face strong influence of the families through the ownership as well as management of the enterprise. The main purpose of our paper is therefore to better understand the association between the degree of involvement of a family in ownership and management of a family enterprise and the business behavior of family enterprise in different business situations. The main data source for our paper is the survey of 350 SMEs in Slovenia. Overall findings suggest that enterprises, characterized by a high degree of family involvement do not differ significantly from the firms that are characterized as non-family ones, regarding the total sales revenues, economic efficiency, value added per employee, export orientation and cooperation with large companies. The same goes for firms characterized with a low degree of family involvement. It is very likely, that in the present state of development of family firms and market economy in Slovenia, the degree of family involvement is not crucial for business behavior and business performance regarding the variables analyzed. Several extensions of our research are also proposed.
Keywords: družinska podjetja; vodenje; poslovna etika